Answer:
No
Step-by-step explanation:
y = 3x + 4 If x=2 And y=10
10 = 3*2 + 4
10 = 10 that’s a solution for this equation
y = x + 7 if x=2 and y=10
10 = 2 + 7
10 (is not) = 9 That’s not a solution for this equation.
Answer:
C. Up.
Step-by-step explanation:
We have been given that the parent function
is transformed to the function
. We are asked to describe the given transformation.
Let us recall the transformation rules.
,
,
,
.
Upon comparing our transformed function with the parent function, we can see that the graph is shifted to left by 7 units and upwards by 5 units.
Therefore the correct choice is option C.
Answer:
Y=60x^(2)-32x+4
Step-by-step explanation:
Y=4(3x-1)(5x-1)
=(12x-4)(5x-1)
=60x^(2)-12x-20x+4
<u>Y=60x^(2)-32x+4</u>
Answer:
12
Step-by-step explanation:
12 +30= 42
42+12=54
Infinite i think. because the two equations are the same.